Analisis Kualitas Pelayanan Parkir Berlangganan di kabupaten Sumedang - Ila Karmila; Fadila Nurfauzia (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The investigation of Sumedang Regency's parking service quality is the main focus of this study. The Sumedang Regency Transportation Service has made adjustments to its implementation in order to meet the goals set forth, one of which being the introduction of subscription parking in April of 2020, or mid-2020. In addition to making parking services more convenient, subscription parking seeks to boost local revenue from the parking retribution industry. Nonetheless, there are still some issues with service in the field as of right now, including unlicensed parking attendants, a decline in the capacity of the road, protests from nearby building or business owners, heavy traffic jams, and people continuing to pay parking fees to the service parking attendants. This study aims to describe the quality of subscription parking services at the Sumedang Regency Transportation Service. This type of research uses descriptive with a qualitative approach. The focus in this study using service quality variables include: 1) Tangibles (Direct Evidence); 2) Reliability (Reliability); 3) Responsiveness (Responsiveness); 4) Assurance (Guarantee); and 5) Empathy (Empathy). The findings show that the following criteria are met: first, responsiveness is demonstrated by the professionalism of the work performed by the officers; second, reliability is demonstrated by the appearance of officers in full uniform and the provision of full service support facilities; third, empathy is demonstrated by the concern of the officers and the application of parking attendants to socialize the use of masks; fourth, assurance is demonstrated by the fact that parking users have rights as per Sumedang Regent Regulation Number 89 of 2022; and fifth, empathy is demonstrated by the concern. However, in its implementation there are still some obstacles so that the Department of Transportation always tries to fix the implementation of subscription parking services in Sumedang Regency.